2022
DOI: 10.3390/pharmaceutics14081552
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking the Intestinal Host–Pathogen Interactions in a 3D In Vitro Model: The Role of the Mucus Layer

Abstract: The intestinal mucus lines the luminal surface of the intestinal epithelium. This mucus is a dynamic semipermeable barrier and one of the first-line defense mechanisms against the outside environment, protecting the body against chemical, mechanical, or biological external insults. At the same time, the intestinal mucus accommodates the resident microbiota, providing nutrients and attachment sites, and therefore playing an essential role in the host–pathogen interactions and gut homeostasis. Underneath this mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…This approach more accurately represents the complex non-flat architecture of the intestinal mucosal environment [ 24 , 25 ]. Caco-2 and HT-29 cells were cultured on hydrogel scaffolds to demonstrate that mucus was a protective factor against bacterial colonization by adherent-invasive E. coli (AIEC) [ 26 ]. Raw and mucin-coated 3D gelatin electrospun membranes were successfully used as scaffolds to culture the human gut microbiota in vitro and reproduce the three-dimensional architecture of the intestinal mucosa and the arrangement of bacteria on it [ 27 , 28 , 29 ].…”
Section: Animal Models or In Vitro Models For Gut Microbiota Research...mentioning
confidence: 99%
“…This approach more accurately represents the complex non-flat architecture of the intestinal mucosal environment [ 24 , 25 ]. Caco-2 and HT-29 cells were cultured on hydrogel scaffolds to demonstrate that mucus was a protective factor against bacterial colonization by adherent-invasive E. coli (AIEC) [ 26 ]. Raw and mucin-coated 3D gelatin electrospun membranes were successfully used as scaffolds to culture the human gut microbiota in vitro and reproduce the three-dimensional architecture of the intestinal mucosa and the arrangement of bacteria on it [ 27 , 28 , 29 ].…”
Section: Animal Models or In Vitro Models For Gut Microbiota Research...mentioning
confidence: 99%
“…[ 55 ] Further, the role of the mucus layer was elucidated by mimicking host‐pathogen interactions in an in vitro model. [ 56 ] Generally, there is a trade‐off between efficiently synthesizing mucus with more accurate material properties and generating the correct mucin composition for the tissue being targeted. This balance has not been fully addressed by existing methods of mucus collection.…”
Section: Current Methods Of Obtaining Mammalian Free‐flowing Mucus An...mentioning
confidence: 99%
“…[322,323] By applying this cocultured cell line, García-Díaz et al successfully built a 3D in vitro model to mimic the in vivo situation, such as physiological dimensions and mechanical properties. [119] By doing so, they found that mucus present in 3D topography can significantly modulate the inter-action between pathogenic E. coli LF82 (AIEC) and the epithelium. Other researchers proposed an approach of using native mucins to form hydrogels from either a mixture of the components from native mucus, or rehydration of purified commercial mucins, i.e., porcine gastric mucin (PGM) and bovine submaxillary mucin (BSM).…”
Section: Mucus Modelsmentioning
confidence: 99%